The Role of Group Dynamics in the Transformation of Society toward Democratic "Solidarity". Issue 1 (2nd January 2018) - Blum, Mark
ABSTRACT: In order to develop the Marxist conception of a "classless society, " one where democratic practices and equality among all its members are realized, one must educate the existing society in interpersonal praxis that generates mutual empathy and cooperation. Once such personal skills are normative for the society, then what many Marxists have understood as a "solidarity society, " a synonym for the classless society, has the foundation it requires. Such a praxis, with its interpersonal communication and cooperation, may be taught using the discipline of group dynamics. Individual conflicts based upon individual differences can gradually be bridged through the practice of dialectical dialogue, in which the engaged communicants learn to formulate personal principles which those who seek cooperative praxis can then reflect upon. Raising personal interests to the level of clear principle enables mutual solutions while respecting areas of valued difference. Such dialectical dialogue is an enhancement of group dynamics as now practiced.